A 3D mutilayer curved plasmonic coupling array with abundant and uniform hot spots for surface-enhanced Raman scattering. (21st November 2019) - Liu, Hanping; Li, Chonghui; Song, Ruihong; Xu, Shicai
Abstract: Abundant and uniform hot spots are of critical importance to an ideal surface-enhanced Raman scattering (SERS) substrate. However, their plasmonic structure still needs to be elaborately designed in detail to obtain the expected sensitive, uniform and reproducible SERS substrate for practical applications. In this study, a self-assembled SiO2 nanosphere array was employed to support a curved graphene@Ag film, and it was further coupled with the dense AuNPs to form a 3D hierarchical AuNPs/curved graphene@Ag film@SiO2 nanosphere array (HACGAA) SERS substrate. The curved structure could provide more landing-points to effectively couple with AuNPs. It not only contributed to the denser hot spots but also induced the synergetic enhancement effect of the bimetal, which was demonstrated in an experiment and a finite-different time-domain theoretical simulation. Based on these results, it was determined that a HACGAA SERS substrate could achieve a sensitive (limit of detection of 10 −11 M for a rhodamine 6G molecule and 10 −9 M for 4-Aminothiophenol), quantitative, uniform, and reproducible analysis, and that it possessed the enormous potential for practical applications.